2023
DOI: 10.1101/2023.03.07.531599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High light can alleviate chilling stress in maize

Abstract: Chilling stress has the potential to significantly decrease growth and yield of sensitive crop plants such as maize. Based on previous work, high light during chilling may exacerbate stress via enhanced photoinhibition but may also aid acclimation responses to chilling. To further understand molecular processes behind responses to chilling with and without high light, two maize accessions with contrasting tolerance (B73 and F7) were exposed to three treatments: chilling, chilling combined with high light and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…From the 188 gene models within the QTL confidence interval (Supplemental Table S4), expression levels of 10 genes were significantly correlated with the founder QTL effects (Supplemental Table S5). These genes included the minor PSII antenna CP24 (lhcb6) expression of which was significantly reduced in F7 based on both RNA-seq data representing all founder lines, as well as based on independent expression data for F7 and B73 (Figure 6C) from Cackett et al, (2023) Since CP24 is known to affect the structure and function of the PSII light harvesting antenna in Arabidopsis (Kovács et al, 2006), we decided to further explore a causative link with the QTL effects observed here. Immunoblot analysis of B73 and F7 using a CP24-specific antibody confirmed that F7 had severely reduced CP24 protein abundance compared to B73 (Figure 6F), which was consistent with a decreased abundance of higher order PSII-LHCII super complexes in blue native PAGE analysis of purified thylakoid membranes from both founder lines (Figure 6G) indicating significant truncation of PSII antenna size associated with the F7 haplotype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 188 gene models within the QTL confidence interval (Supplemental Table S4), expression levels of 10 genes were significantly correlated with the founder QTL effects (Supplemental Table S5). These genes included the minor PSII antenna CP24 (lhcb6) expression of which was significantly reduced in F7 based on both RNA-seq data representing all founder lines, as well as based on independent expression data for F7 and B73 (Figure 6C) from Cackett et al, (2023) Since CP24 is known to affect the structure and function of the PSII light harvesting antenna in Arabidopsis (Kovács et al, 2006), we decided to further explore a causative link with the QTL effects observed here. Immunoblot analysis of B73 and F7 using a CP24-specific antibody confirmed that F7 had severely reduced CP24 protein abundance compared to B73 (Figure 6F), which was consistent with a decreased abundance of higher order PSII-LHCII super complexes in blue native PAGE analysis of purified thylakoid membranes from both founder lines (Figure 6G) indicating significant truncation of PSII antenna size associated with the F7 haplotype.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Chromosome 10 QTL for Fv/Fm (B) Founder QTL effects at chromosome ten QTL (C) Difference in expression of CP24 between B73 and F7 from Cackett et al . (2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations